IMPLEMENTATION OF LIFELONG LEARNING COMPETENCIES THROUGH LITERACY PROGRAM IN THE SCHOOL LIBRARY MA SULAMUL HUDA MLARAK PONOROGO - Nur kolis; Idris Akbar Pramono (Universitas Muhammadiyah Surabaya, 2023)
Lifelong learning can be developed through literacy programs in school libraries. This study aims to determine the implementation of lifelong learning competencies through literacy programs in the school library. The research method uses a qualitative approach through descriptive research methods to librarians, four teachers, and 25 students at MA Sulamul Huda Mlarak Ponorogo, East Java. Through observation, data collection techniques were carried out using a checklist form for the dimensions of lifelong learning, semi-structured and in-depth interviews, and literature studies. Data analysis technique is data reduction using open coding, data presentation, and drawing conclusions. The results of the study show that librarians organize literacy programs that support the School Literacy Movement. In practice, librarians act as initiators; teachers become facilitators and librarian partners in developing literacy programs in schools. Literacy programs have a positive impact on students, including building character, increasing knowledge, developing special talents related to communication and writing, adding experience, building positive relationships between librarians and students, and intellectual recreation. Communication competence in a foreign language is one of the lifelong learning competencies that is not accommodated by the school library program. The obstacle to the literacy program is managing study time and the role of parents and family at home. This study concludes that school library literacy programs have supported increased implementation of lifelong learning competencies for students in several dimensions.Â Keywords: Literacy program; Lifelong learning; School library; School literacy movement; Librarian.